Skip to main content

Enlarged integral inequalities through recent fractional generalized operators

Abstract

This paper is devoted to proving some new fractional inequalities via recent generalized fractional operators. These inequalities are in the Hermite–Hadamard and Minkowski settings. Many previously documented inequalities may clearly be deduced as specific examples from our findings. Moreover, we give some comparative remarks to show the advantage and novelty of the obtained results.

Introduction

Fractional integral inequalities are very important in theoretical mathematics and are a substantial tool in dealing with fractional calculus science, which plays a vital role in modeling procedures for a variety of engineering issues [1, 14, 18, 24, 32]. Many fractional models yield better outcomes than identical equivalent models with integer derivatives, as illustrated in [27]. This drives the need for more exact inequalities when working with fractional calculus-based mathematical models. In the existing modification of a certain study, we concentrate on the most prominent Hermite–Hadamard-type inequality [2, 8]. Because of the nature of its definition, convexity is crucial in analyzing inequality for convex functions; for other classes of convex functions and attributes; see [5, 15, 16, 19, 20, 25, 26].

Recently, generalized fractional operators have been used to construct a Hermite–Hadamard-type inequality allowing the ordinary version to be regained in its limit for the generalized fractional parameter, as shown in [1]. In [7] a generalized k-fractional integral inequality is proposed, as well as the Minkowski and Chebyshev integral inequalities that involve the generalized k-fractional integrals. Inequalities of Hermite–Hadamard type under generalized k-fractional integrals were studied in [9]. Guessab and Schmeisser [6] examined the sharp integral inequalities of the Hermite–Hadamard type. Also, Nisar et al. [22] employed the Minkowski and Hermite–Hadamard inequalities to expand the results of Dahmani [4] and proposed a more powerful integral inequality. Hyder et al. [12] utilized some generalized fractional integrals to examine specific fractional-order inequalities in Minkowski and Hermite–Hadamard manners.

Let us start with the traditional Hermite–Hadamard inequality: If \(u:B \subseteq \mathbb{R}\rightarrow \mathbb{R}\) is a convex function and \(\delta _{1},\delta _{2}\in B\) with \(\delta _{1}<\delta _{2}\),then

$$\begin{aligned} u \biggl(\frac{\delta _{1}+\delta _{2}}{2} \biggr) \leq \frac{1}{\delta _{2}-\delta _{1}} \int _{\delta _{1}}^{\delta _{2}} u( \tau ) \,d \tau \leq \frac{f(\delta _{1})+f(\delta _{2})}{2}. \end{aligned}$$
(1)

Additional generalizations and expansions can be found, for instance, in [21, 23, 28, 30]. Moreover, we can begin by recalling some basic fractional notions.

Definition 1.1

([27])

The Riemann–Liouville fractional left and right integrals of a function H are respectively defined by

$$\begin{aligned} \mathfrak{J}_{x^{+}}^{\gamma} H(t)= \frac{1}{\Gamma (\gamma )} \int _{x}^{t}(t- \tau )^{\gamma -1} H(\tau ) \,d \tau\quad \bigl(t>x, \mathrm{Re}(\gamma )>0\bigr) \end{aligned}$$
(2)

and

$$\begin{aligned} \mathfrak{J}_{y^{-}}^{\gamma} H(t)= \frac{1}{\Gamma (\gamma )} \int _{t}^{y}( \tau -t)^{\gamma -1} H(\tau ) \,d \tau\quad \bigl(t< y, \mathrm{Re}(\gamma )>0\bigr) , \end{aligned}$$
(3)

where Γ is the gamma function.

Definition 1.2

([13])

The left and right fractional obedient (conformable) integral operators are respectively defined by

$$\begin{aligned} {}^{\lambda} \mathfrak{J}_{x^{+}}^{\gamma} H(t)= \frac{1}{\Gamma (\gamma )} \int _{x}^{t} \biggl( \frac{(t-x)^{\gamma}-(\tau -x)^{\gamma}}{\gamma} \biggr)^{\lambda -1} \frac{H(\tau )}{(\tau -x)^{1-\gamma}} \,d \tau,\quad t>x , \end{aligned}$$
(4)

and

$$\begin{aligned} {}^{\lambda} \mathfrak{J}_{y^{-}}^{\gamma} H(t)= \frac{1}{\Gamma (\gamma )} \int _{t}^{y} \biggl( \frac{(y-t)^{\gamma}-(y-\tau )^{\gamma}}{\gamma} \biggr)^{\lambda -1} \frac{H(\tau )}{(y-\tau )^{1-\gamma}} \,d \tau,\quad t< y, \end{aligned}$$
(5)

where \(\lambda \in \mathbb{C}\) with \(\mathrm{Re}(\lambda )>0\).

Hyder and Barakat [10] enhanced the fractional obedient integral operators and offered more general definitions of the fractional integral operators as follows.

Definition 1.3

The general improved fractional left and right integral operators of a function H are respectively given by

$$\begin{aligned} {}^{\lambda} \mathfrak{J}_{x^{+}}^{\gamma} H(t)= \frac{1}{\Gamma (\gamma )} \int _{x}^{t}h^{\lambda -1}(t-x,\tau -x, \gamma ) \frac{H(\tau )}{\vartheta (\tau -x,\gamma )} \,d\tau,\quad t>x, \end{aligned}$$
(6)

and

$$\begin{aligned} {}^{\lambda} \mathfrak{J}_{y^{-}}^{\gamma} H(t)= \frac{1}{\Gamma (\gamma )} \int _{t}^{y}h^{\lambda -1}(y-t, y-\tau, \gamma ) \frac{H(\tau )}{\vartheta (y-\tau,\gamma )} \,d \tau,\quad t< y, \end{aligned}$$
(7)

where

$$\begin{aligned} h(t, \tau, \gamma )= \int _{\tau}^{t} \frac{d \tau ^{*}}{\vartheta (\tau ^{*}, \gamma )}, \end{aligned}$$
(8)

and \(\vartheta:\mathbb{R}_{+} \times (0,1]\rightarrow \mathbb{R}_{+}\) is a continuous function fulfilling the conditions:

  • \(\vartheta (t,1)=1\) \(\forall t\in \mathbb{R}_{+}\),

  • \(\vartheta (t,\gamma )\neq 0\) \(\forall (t,\gamma )\in \mathbb{R}_{+}\times (0,1]\),

  • \(\vartheta (\cdot,\gamma _{1})\neq \vartheta (\cdot,\gamma _{2})\) \(\forall \gamma _{1},\gamma _{2}\in [0,1]\).

In 2020, Hyder and Soliman [11] introduced the new generalized theta-obedient integral

$$\begin{aligned} \mathfrak{J}^{\gamma}_{\theta,q}H(t)= \int _{0}^{t} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma ))H(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau,\quad t \in \mathbb{R}_{+}, \end{aligned}$$
(9)

where \(\tau \neq q\in \mathbb{R}\mathbbm{,}\) and \(\theta _{q}:\mathbb{R}_{+}\times (0,1]\rightarrow \mathbb{R}\) is a continuous function satisfying the following conditions:

  • \(\theta _{q}(t,1)=1\) \(\forall t\in \mathbb{R}_{+}\),

  • \(\theta _{q}(t,\gamma )\neq 0\) \(\forall (t,\gamma )\in \mathbb{R}_{+}\times (0,1]\),

  • \(\theta _{q}(\cdot,\gamma _{1})\neq \theta _{q}(\cdot,\gamma _{2})\) \(\forall \gamma _{1},\gamma _{2}\in [0,1]\),

  • \(\theta _{0}(t,\gamma )=\vartheta (t,\gamma )\) \(\forall (t,\gamma )\in \mathbb{R}_{+}\times (0,1]\).

Using the Cauchy formula for iterated integrals, we can iterate the integral (9) n times and obtain the following result:

$$\begin{aligned} {}^{n}\mathfrak{J}^{\gamma}_{\theta,q}H(t)={}& \int _{0}^{t} \frac{(\tau _{1}-q(1+\theta _{q}(\tau _{1},\gamma ))\,d\tau _{1}}{(\tau _{1}-q)\theta _{q}(\tau _{1},\gamma )} \int _{0}^{\tau _{1}} \frac{(\tau _{2}-q(1+\theta _{q}(\tau _{2},\gamma ))\,d\tau _{2}}{(\tau _{2}-q)\theta _{q}(\tau _{2},\gamma )} \\ &\cdots \int _{0}^{\tau _{n-1}} \frac{(\tau _{n}-q(1+\theta _{q}(\tau _{n},\gamma ))H(\tau _{n})}{(\tau _{n}-q)\theta _{q}(\tau _{n},\gamma )}\,d \tau _{n} \\ ={}&\frac{1}{\Gamma (n)} \int _{0}^{t} g_{q}^{n-1}(t, \tau,\gamma ) \frac{(\tau -q(1+\theta _{q}(\tau,\gamma ))H(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau, \end{aligned}$$
(10)

where

$$\begin{aligned} g_{q}(t,\tau,\gamma )= \int _{\tau}^{t} \frac{(u-q(1+\theta _{q}(u,\gamma ))}{(u-q)\theta _{q}(u,\gamma )}\,du. \end{aligned}$$
(11)

Replacing the natural number n by a complex number λ, we define the generalized fractional theta-obedient integral as follows.

Definition 1.4

The generalized fractional theta-obedient integral of a function H is defined by

$$\begin{aligned} {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q}H(t)= \frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1} (t,\tau, \gamma ) \frac{(\tau -q(1+\theta _{q}(\tau,\gamma ))H(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau, \end{aligned}$$
(12)

where \(\lambda \in \mathbb{C}\) with \(\mathrm{Re}(\lambda )>0\), and \(g_{q}\) is defined by (11).

In this paper, we employ recently developed generalized fractional operators to construct novel fractional inequalities for integrable nonnegative functions. These inequalities concern the Hermite–Hadamard and Minkowski inequalities. Our outcomes can be compared by the previous results established in [3, 12, 22]. The inequalities obtained in these references can be derived as particular cases. Also, we show in this work that the inequality of [22, Theorem 2.5] is incorrect. Finally, this paper is organized as follows: Sect. 2 contains the main results, and Sect. 3 provides concluding remarks.

Main results

In this section, we establish generalized fractional inequalities in the Hermite–Hadamard and Minkowski settings using newly discovered fractional integral operators. To support this claim, we offer the following theorems.

Theorem 2.1

Let \(\lambda,\gamma >0\) and \(s\geq 1\), and let H, B be two functions on \([0,\infty )\) such that for all \(t>0\), \(H(t), B(t)>0\),\({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t)<\infty \), and \({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t)<\infty \). If \(0< j\leq \frac{H(\tau )}{B(\tau )}\leq J\), \(\tau \in [0,t]\), and \(\tau \geq q(1+\theta _{q}(\tau,\gamma ))\), then we have the following inequality:

$$\begin{aligned} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t) \bigr)^{1/s}+ \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t) \bigr)^{1/s} \leq \frac{1+(j+2)J}{(j+1)(J+1)} \bigl({}^{\lambda} \mathfrak{J}^{ \gamma}_{\theta,q} (H+B )^{s}(t) \bigr)^{1/s}. \end{aligned}$$
(13)

Proof

According to the condition \(\frac{H(\tau )}{B(\tau )}\leq J\), \(\tau \in [0,t],t>0\), we get

$$\begin{aligned} (J+1)^{s} H^{s}(\tau )\leq J^{s}(H+B)^{s}(\tau ). \end{aligned}$$
(14)

Therefore we have

$$\begin{aligned} &\frac{(J+1)^{s}}{\Gamma (\lambda )}g_{q}^{\lambda -1}(t, \tau,\gamma ) \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))H^{s}(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )} \\ &\quad \leq \frac{J^{s}}{\Gamma (\lambda )}g_{q}^{\lambda -1}(t, \tau, \gamma ) \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))(H+B)^{s}(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )}. \end{aligned}$$
(15)

Using (12), we can integrate inequality (15) from 0 to t with respect to τ:

$$\begin{aligned} {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t)\leq \frac{J^{s}}{(J+1)^{s}} {}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} (H+B)^{s}(t). \end{aligned}$$
(16)

Hence

$$\begin{aligned} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t) \bigr)^{1/s} \leq \frac{J}{J+1} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} (H+B)^{s}(t) \bigr)^{1/s}. \end{aligned}$$
(17)

Now, according to the condition \(\frac{H(\tau )}{B(\tau )}\geq j\), we have

$$\begin{aligned} \biggl(1+\frac{1}{j} \biggr)^{s} B^{s}(\tau )\leq \biggl( \frac{1}{j} \biggr)^{s}(H+B)^{s}( \tau ) \end{aligned}$$
(18)

and

$$\begin{aligned} &\frac{1}{\Gamma (\lambda )} \biggl(1+\frac{1}{j} \biggr)^{s} g_{q}^{ \lambda -1}(t,\tau,\gamma ) \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))B^{s}(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )} \\ &\quad \leq \frac{1}{\Gamma (\lambda )} \biggl(\frac{1}{j} \biggr)^{s} g_{q}^{ \lambda -1}(t,\tau,\gamma ) \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))(H+B)^{s}(\tau )}{(\tau -q)\theta _{q}(\tau,\gamma )}. \end{aligned}$$
(19)

Using (14), we can integrate inequality (19) from 0 to t with respect to τ:

$$\begin{aligned} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t) \bigr)^{1/s} \leq \frac{1}{j+1} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} (H+B)^{s}(t) \bigr)^{1/s}. \end{aligned}$$
(20)

Thus by adding inequalities (17) and (20) we obtain the required inequality (13). □

Theorem 2.2

Let \(\gamma >0\), \(s\geq 1\), and \(\lambda \in \mathbb{C}\), \(\mathrm{Re}( \lambda )>0\), and let \(H,B\) be two functions on \([0,\infty )\) such that for all \(t>0\), \(H(t),B(t)>0\), \({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t)<\infty \), and \({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t)<\infty \). If \(0< j\leq \frac{H(\tau )}{B(\tau )}\leq J\), \(\tau \in [0,t]\), and \(\tau \geq q(1+\theta _{q}(\tau,\gamma ))\), then we have the following inequality:

$$\begin{aligned} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t) \bigr)^{2/s}+ \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t) \bigr)^{2/s} \geq \biggl(\frac{(J+1)(j+1)}{J}-2 \biggr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} (H+B )^{s}(t) \bigr)^{1/s}. \end{aligned}$$
(21)

Proof

By multiplying the two inequalities (17) and (20) we get

$$\begin{aligned} \biggl(\frac{(J+1)(j+1)}{J} \biggr) \bigl({}^{\lambda} \mathfrak{J}^{ \gamma}_{\theta,q} H^{s}(t) \bigr)^{1/s} \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t) \bigr)^{1/s} \leq \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} (H+B)^{s}(t) \bigr)^{2/s}. \end{aligned}$$
(22)

By the Minkowski inequality we obtain

$$\begin{aligned} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} (H+B)^{s}(t) \bigr)^{2/s} \leq {}& \bigl( \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{ \theta,q} H^{s}(t) \bigr)^{1/s}+ \bigl({}^{\lambda} \mathfrak{J}^{ \gamma}_{\theta,q} B^{s}(t) \bigr)^{1/s} \bigr)^{2} \\ ={}& \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t) \bigr)^{2/s}+ \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t) \bigr)^{2/s} \\ &{}+2 \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} H^{s}(t) \bigr)^{1/s} \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} B^{s}(t) \bigr)^{1/s}. \end{aligned}$$
(23)

Thus we can derive the desired inequality (21) using inequalities (22) and (23). □

Lemma 2.1

([4])

Let H be a concave function on \([a,b]\). Then we have the following inequalities:

$$\begin{aligned} H(a)+H(b)\leq H(a+b-t)+H(t)\leq 2H \biggl(\frac{a+b}{2} \biggr). \end{aligned}$$
(24)

Theorem 2.3

Let \(\lambda,\gamma >0\), \(\lambda \in \mathbb{C}\), and \(c,d>1\), and let \(H,B\) be two functions on \([0,\infty )\) such that \(H(t),B(t)>0\) for \(t>0\). If the functions \(H^{c},B^{d}\) are concave on \([0,\infty )\), then we have the following inequality:

$$\begin{aligned} &\frac{1}{2^{c+d}} \bigl(H(0)+H\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr)^{c} \bigl(B(0)+B\bigl( \gamma g_{q}(t,0,\gamma )\bigr) \bigr)^{d} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl(\gamma ^{\lambda -1}g_{q}^{\lambda -1}(t,0,\gamma ) \bigr) \bigr)^{2} \\ &\quad \leq {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \gamma ^{ \lambda -1}g_{q}^{\lambda -1}(t,0,\gamma )H^{c}\bigl(\gamma g_{q}(t,0, \gamma )\bigr) \bigr){}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \\ &\qquad{}\times \bigl( \gamma ^{\lambda -1}g_{q}^{\lambda -1}(t,0,\gamma )B^{d}\bigl(\gamma g_{q}(t,0, \gamma )\bigr) \bigr). \end{aligned}$$
(25)

Proof

By Lemma 2.1 and the concavity of the functions \(H^{c},B^{d}\), for \(t>0,\gamma >0\), and \(\tau \in [0,t]\), we have

$$\begin{aligned} H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma )\bigr)&\leq H^{c}\bigl(\gamma g_{q}(t, \tau,\gamma )\bigr)+H^{c}\bigl(\gamma g_{q}(\tau,0,\gamma )\bigr) \\ &\leq 2H^{c}\biggl( \frac{\gamma}{2} g_{q}(t,0,\gamma )\biggr), \end{aligned}$$
(26)
$$\begin{aligned} B^{d}(0)+B^{d}\bigl(\gamma g_{q}(t,0,\gamma )\bigr)&\leq B^{d}\bigl(\gamma g_{q}(t, \tau,\gamma )\bigr)+B^{d}\bigl(\gamma g_{q}(\tau,0,\gamma )\bigr) \\ &\leq 2B^{d}\biggl( \frac{\gamma}{2} g_{q}(t,0,\gamma )\biggr). \end{aligned}$$
(27)

Multiplying inequalities (26) and (27) by \(\frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{\Gamma (\lambda )(\tau -q)\theta _{q}(\tau,\gamma )} (\gamma g_{q}(t,\tau,\gamma )g_{q}(\tau,0,\gamma ) )^{ \lambda -1}\) and integrating the resulting inequalities from 0 to t, we get

$$\begin{aligned} &\frac{H^{c}(0)+H^{c}(\gamma g_{q}(t,0,\gamma ))}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{\tau -q(1+\theta _{q}(\tau,\gamma ))\,d\tau}{(\tau -q)\theta _{q}(\tau,\gamma )} \\ &\quad \leq \frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))H^{c}(\gamma g_{q}(t,\tau,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\qquad{}+\frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))H^{c}(\gamma g_{q}(\tau,0,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\quad \leq \frac{2 H^{c} (\frac{\gamma}{2}g_{q}(t,0,\gamma ) )}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0, \gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))\,d\tau}{(\tau -q)\theta _{q}(\tau,\gamma )}, \end{aligned}$$
(28)

and

$$\begin{aligned} &\frac{B^{d}(0)+B^{d}(\gamma g_{q}(t,0,\gamma ))}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))\,d\tau}{(\tau -q)\theta _{q}(\tau,\gamma )} \\ &\quad \leq \frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))B^{d}(\gamma g_{q}(t,\tau,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\qquad{}+\frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))B^{d}(\gamma g_{q}(\tau,0,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\quad \leq \frac{2 B^{d} (\frac{\gamma}{2}g_{q}(t,0,\gamma ) )}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0, \gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))\,d\tau}{(\tau -q)\theta _{q}(\tau,\gamma )}. \end{aligned}$$
(29)

Setting \(g_{q}(t,\tau,\gamma )=g_{q}(\eta,0,\gamma )\), we have

$$\begin{aligned} &\frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau, \gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))\,d\tau}{(\tau -q)\theta _{q}(\tau,\gamma )} \\ &\quad= {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\lambda -1} \bigr), \end{aligned}$$
(30)
$$\begin{aligned} &\frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))H^{c}(\gamma g_{q}(t,\tau,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d\tau \\ &\quad= {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\lambda -1}H^{c}\bigl( \gamma g_{q}(t,0,\gamma ) \bigr), \end{aligned}$$
(31)

and

$$\begin{aligned} &\frac{1}{\Gamma (\lambda )} \int _{0}^{t} \bigl(\gamma g_{q}(t, \tau,\gamma )g_{q}(\tau,0,\gamma ) \bigr)^{\lambda -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))B^{d}(\gamma g_{q}(t,\tau,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d\tau \\ &\quad= {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\lambda -1}B^{d}\bigl( \gamma g_{q}(t,0,\gamma ) \bigr). \end{aligned}$$
(32)

Therefore by (28), (30), and (31) we get

$$\begin{aligned} & (H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr) \\ &\quad \leq 2 {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1}H^{c} \bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \\ &\quad \leq 2H^{c} \biggl(\frac{\gamma}{2}g_{q}(t,0, \gamma ) \biggr) \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr), \end{aligned}$$
(33)

and by (29), (30), and (32) we get

$$\begin{aligned} & (B^{d}(0)+B^{d}\bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr) \\ &\quad \leq 2 {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1}B^{d} \bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \\ &\quad \leq 2B^{d} \biggl(\frac{\gamma}{2}g_{q}(t,0, \gamma ) \biggr) \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr). \end{aligned}$$
(34)

Hence by multiplying both inequalities (33) and (34) it follows that

$$\begin{aligned} & (H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma ) \bigr) (B^{d}(0)+B^{d} \bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr)^{2} \\ &\quad \leq 4 ({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1}H^{c} \bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \bigr) \\ &\qquad{}\times ({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1}B^{d} \bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \bigr). \end{aligned}$$
(35)

Since \(H(t)B(t)>0\) for \(t>0\), for \(\gamma >0,c\geq 0\), and \(d\geq 0\), we have

$$\begin{aligned} \biggl(\frac{H^{c}(0)+H^{c}(\gamma g_{q}(t,0,\gamma )}{2} \biggr)^{1/c} \geq \frac{H(0)+H(\gamma g_{q}(t,0,\gamma )}{2}, \end{aligned}$$
(36)

and

$$\begin{aligned} \biggl(\frac{B^{d}(0)+B^{d}(\gamma g_{q}(t,0,\gamma )}{2} \biggr)^{1/d} \geq \frac{B(0)+B(\gamma g_{q}(t,0,\gamma )}{2}. \end{aligned}$$
(37)

Therefore

$$\begin{aligned} & \biggl(\frac{H^{c}(0)+H^{c}(\gamma g_{q}(t,0,\gamma )}{2} \biggr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr) \\ &\quad \geq \biggl(\frac{H(0)+H(\gamma g_{q}(t,0,\gamma )}{2} \biggr)^{c} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr) , \end{aligned}$$
(38)

and

$$\begin{aligned} & \biggl(\frac{B^{d}(0)+B^{d}(\gamma g_{q}(t,0,\gamma )}{2} \biggr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr) \\ &\quad \geq \biggl(\frac{B(0)+B(\gamma g_{q}(t,0,\gamma )}{2} \biggr)^{d} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr). \end{aligned}$$
(39)

Using inequalities (38) and (39), we obtain

$$\begin{aligned} & (H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma ) \bigr) (B^{d}(0)+B^{d} \bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr)^{2} \\ &\quad \geq 2^{2-c-d} (H(0)+H\bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{c} (B(0)+B\bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{d} \\ &\qquad{}\times \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr)^{2}. \end{aligned}$$
(40)

Hence we derive the needed inequality (25) by combining inequalities (35) and (40). □

Theorem 2.4

Let \(\lambda,\gamma, \nu >0\), \(\lambda,\nu \in \mathbb{C}\), and \(c,d>1\), and let \(H,B\) be two functions on \([0,\infty )\) such that \(H(t),B(t)>0\) for \(t>0\). If \(H^{c},B^{d}\) are concave on \([0,\infty )\), then we have the following inequality:

$$\begin{aligned} &\frac{1}{2^{c+d-2}} \bigl(H(0)+H(t) \bigr)^{c} \bigl(B(0)+B(t) \bigr)^{d} \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl(\gamma ^{\nu -1}g_{q}^{\nu -1}(t,0, \gamma ) \bigr) \bigr)^{2} \\ &\quad \leq \biggl[ \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} \bigl(\gamma ^{\lambda -1}g_{q}^{\lambda -1}(t,0, \gamma )H^{c}\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \\ &\qquad{}+{}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl(\gamma ^{\nu -1}g_{q}^{ \nu -1}(t,0,\gamma )H^{c}\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \biggr] \\ &\qquad{}\times \biggl[ \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} \bigl(\gamma ^{\lambda -1}g_{q}^{\lambda -1}(t,0, \gamma )B^{d}\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \\ &\qquad{}+ {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl(\gamma ^{\nu -1}g_{q}^{ \nu -1}(t,0,\gamma )B^{d}\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \biggr]. \end{aligned}$$
(41)

Proof

Multiplying inequalities (26) and (27) by \(\frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{\Gamma (\lambda )(\tau -q)\theta _{q}(\tau,\gamma )} g_{q}^{\lambda -1}(t,\tau,\gamma ) (\gamma g_{q}(\tau,0, \gamma ) )^{\nu -1}\) and then integrating the resulting inequalities with respect to τ from 0 to t, we obtain

$$\begin{aligned} &\frac{H^{c}(0)+H^{c}(\gamma g_{q}(t,0,\gamma ))}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1}\frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d\tau \\ &\quad \leq \frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))H^{c}(\gamma g_{q}(t,\tau,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau\, d\tau \\ &\qquad{}+\frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))H^{c}(\gamma g_{q}(\tau,0,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\quad \leq \frac{2 H^{c} (\frac{\gamma}{2}g_{q}(t,0,\gamma ) )}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}( \tau,0,\gamma ) \bigr)^{\nu -1} \frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau, \end{aligned}$$
(42)

and

$$\begin{aligned} &\frac{B^{d}(0)+B^{d}(\gamma g_{q}(t,0,\gamma ))}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1}\frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d\tau \\ &\quad \leq \frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))B^{d}(\gamma g_{q}(t,\tau,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau\, d\tau \\ &\qquad{}+\frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1} \frac{(\tau -q(1+\theta _{q}(\tau,\gamma )))B^{d}(\gamma g_{q}(\tau,0,\gamma )}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\quad \leq \frac{2 B^{d} (\frac{\gamma}{2}g_{q}(t,0,\gamma ) )}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}( \tau,0,\gamma ) \bigr)^{\nu -1} \frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau. \end{aligned}$$
(43)

Setting \(g_{q}(t,\tau,\gamma )=g_{q}(\eta,0,\gamma )\),we have

$$\begin{aligned} & \frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau, \gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1} \frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d \tau \\ &\quad= {}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\nu -1} \bigr), \end{aligned}$$
(44)
$$\begin{aligned} &\frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1}H^{c}(\gamma g_{q}(t,\tau,\gamma )\frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}\,d\tau \\ &\quad=\frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{ \nu}\mathfrak{J}^{\gamma} ( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1}H^{c} \bigl(\gamma g_{q}(t,0,\gamma ) \bigr), \end{aligned}$$
(45)

and

$$\begin{aligned} &\frac{1}{\Gamma (\lambda )} \int _{0}^{t} g_{q}^{\lambda -1}(t, \tau,\gamma ) \bigl(\gamma g_{q}(\tau,0,\gamma ) \bigr)^{\nu -1}\frac{\tau -q(1+\theta _{q}(\tau,\gamma ))}{(\tau -q)\theta _{q}(\tau,\gamma )}B^{d}(\gamma g_{q}(t,\tau,\gamma )\,d\tau \\ &\quad=\frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{ \nu}\mathfrak{J}^{\gamma} ( \bigl( \gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1}B^{d} \bigl(\gamma g_{q}(t,0,\gamma ) \bigr). \end{aligned}$$
(46)

Therefore, by (41), (44), and (45) we get

$$\begin{aligned} & (H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\nu -1} \bigr) \bigr) \\ &\quad \leq \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} ( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{ \lambda -1}H^{c}\bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \\ &\qquad{}+{}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\nu -1}H^{c}\bigl( \gamma g_{q}(t,0,\gamma ) \bigr). \end{aligned}$$
(47)

Also, by (43), (44), and (46) we get

$$\begin{aligned} & (B^{d}(0)+B^{d}\bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\nu -1} \bigr) \bigr) \\ &\quad \leq \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} ( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{ \lambda -1}B^{d}\bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \\ &\qquad{}+{}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\nu -1}B^{d}\bigl( \gamma g_{q}(t,0,\gamma ) \bigr). \end{aligned}$$
(48)

By multiplying inequalities (47) and (48) we get

$$\begin{aligned} & \bigl(H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \bigl(B^{d}(0)+B^{d} \bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\nu -1} \bigr) \bigr)^{2} \\ &\quad \leq \biggl[ \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} ( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{ \lambda -1}H^{c}\bigl(\gamma g_{q}(t,0, \gamma ) \bigr) \\ &\qquad{}+{}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\nu -1}H^{c}\bigl( \gamma g_{q}(t,0,\gamma ) \bigr) \biggr] \end{aligned}$$
(49)
$$\begin{aligned} &\quad \leq \biggl[ \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} ( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{ \lambda -1}B^{d} \bigl(\gamma g_{q}(t,0,\gamma ) \bigr) \\ &\qquad{}+{}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} ( \bigl(\gamma g_{q}(t,0, \gamma ) \bigr)^{\nu -1}B^{d}\bigl( \gamma g_{q}(t,0,\gamma ) \bigr) \biggr]. \end{aligned}$$
(50)

According to inequalities (38) and (39), we obtain

$$\begin{aligned} &\bigl(H^{c}(0)+H^{c}\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \bigl(B^{d}(0)+B^{d} \bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr) \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr)^{\lambda -1} \bigr) )^{2} \\ &\quad \geq 2^{2-k-l} \bigl(H(0)+H\bigl(\gamma g_{q}(t,0, \gamma )\bigr) \bigr)^{c} \bigl(B(0)+B\bigl(\gamma g_{q}(t,0,\gamma )\bigr) \bigr)^{d} \\ &\qquad{}\times \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta,q} \bigl( \bigl(\gamma g_{q}(t,0,\gamma ) \bigr)^{\lambda -1} \bigr) \bigr)^{2}. \end{aligned}$$
(51)

Hence we derive the needed inequality (41) by combining inequalities (49) and (51). □

Comparative cases

In this study, we establish the Hermite–Hadamard and Minkowski inequalities in the context of newly generalized fractional integral operators.

We examine some specific cases arising from our findings in this section by presenting some particular examples of our fractional integral operator described by equation (12) as the following cases.

Case I. If we put \(q=0\) in (12), then we get the general improved fractional operator defined in [10]. When this operator is applied to the Hermite–Hadamard and Minkowski inequalities, the obtained results are reduced to the following corollaries.

Corollary 3.1

Let \(\lambda,\gamma >0\), \(\lambda \in \mathbb{C}\), and \(c,d>1\). Let \(H,B\) be two functions on \([0,\infty )\) such that \(H(t),B(t)>0\) for \(t>0\). If the functions \(H^{c},B^{d}\) are concave on \([0,\infty )\), then we have the following inequality:

$$\begin{aligned} &\frac{1}{2^{c+d}} \bigl(H(0)+H\bigl(\gamma g(t,0,\gamma ) \bigr) \bigr)^{c} \bigl(B(0)+B\bigl(\gamma g(t,0,\gamma )\bigr) \bigr)^{d} \bigl({}^{\lambda}\mathfrak{J}^{\gamma}_{\theta} \bigl(\gamma ^{\lambda -1}g^{\lambda -1}(t,0,\gamma ) \bigr) \bigr)^{2} \\ &\quad \leq {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta} \bigl( \gamma ^{ \lambda -1}g^{\lambda -1}(t,0,\gamma )H^{c}\bigl( \gamma g(t,0,\gamma )\bigr) \bigr){}^{\lambda}\mathfrak{J}^{\gamma}_{\theta} \bigl(\gamma ^{ \lambda -1}g^{\lambda -1}(t,0,\gamma )B^{d} \bigl(\gamma g(t,0,\gamma )\bigr) \bigr). \end{aligned}$$
(52)

Corollary 3.2

Let \(\lambda,\gamma, \nu >0\), \(\lambda,\nu \in \mathbb{C}\), and \(c,d>1\), and let \(H,B\) be two functions on \([0,\infty )\) such that \(H(t),B(t)>0\) for \(t>0\). If \(H^{c},B^{d}\) are concave functions on \([0,\infty )\), then we have the following inequality:

$$\begin{aligned} &\frac{1}{2^{c+d-2}} \bigl(H(0)+H(t) \bigr)^{c} \bigl(B(0)+B(t) \bigr)^{d} \bigl({}^{\lambda} \mathfrak{J}^{\gamma}_{\theta} \bigl(\gamma ^{\nu -1}g^{\nu -1}(t,0, \gamma ) \bigr) \bigr)^{2} \\ &\quad \leq \biggl[ \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} \bigl(\gamma ^{\lambda -1}g^{\lambda -1}(t,0, \gamma )H^{c} \bigl(\gamma g(t,0,\gamma )\bigr) \bigr) \\ &\qquad{}+{}^{\lambda}\mathfrak{J}^{\gamma}_{\theta} \bigl(\gamma ^{\nu -1}g^{ \nu -1}(t,0,\gamma )H^{c}\bigl(\gamma g(t,0,\gamma )\bigr) \bigr) \biggr] \\ &\qquad{}\times \biggl[ \frac{\gamma ^{\nu -\lambda}\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{\gamma} \bigl(\gamma ^{\lambda -1}g^{\lambda -1}(t,0, \gamma )B^{d} \bigl(\gamma g(t,0,\gamma )\bigr) \bigr) \\ &\qquad{}+ {}^{\lambda}\mathfrak{J}^{\gamma}_{\theta} \bigl(\gamma ^{\nu -1}g^{ \nu -1}(t,0,\gamma )B^{d}\bigl(\gamma g(t,0,\gamma )\bigr) \bigr) \biggr]. \end{aligned}$$
(53)

Case II. If we put \(\gamma = 1\) and \(g(t,\tau, \gamma )=\ln t- \ln \tau \) in Corollary 3.2, then we obtain the integral inequalities due to Hadamard fractional integral operator as follows.

Corollary 3.3

Let \(\lambda, \nu >0\), \(\lambda,\nu \in \mathbb{C}\), and \(k,l>1\), and let \(H,B\) be two functions on \([0,\infty )\) such that \(H(t),B(t)>0\) for \(t>0\). If \(H^{c},B^{d}\) are concave functions on \([0,\infty )\), then we have the following inequality:

$$\begin{aligned} &\frac{1}{2^{k+l-2}} \bigl(H(0)+H(t) \bigr)^{c} \bigl(B(0)+B(t) \bigr)^{d} \bigl({}^{\lambda} \mathfrak{J}^{1} \bigl((\ln t) ^{\nu -1}\bigr) \bigr)^{2} \\ &\quad \leq \biggl[\frac{\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{1} \bigl((\ln t)^{\lambda -1} H^{c}( \ln t) \bigr)+ ^{ \lambda}\mathfrak{J}^{1}((\ln t)^{\nu -1}H^{c}( \ln t) \biggr] \\ &\qquad{}\times \biggl[\frac{\Gamma (\nu )}{\Gamma (\lambda )} ^{\nu} \mathfrak{J}^{1} \bigl((\ln t) ^{\lambda -1} B^{d}( \ln t) \bigr)+ ^{ \lambda}\mathfrak{J}^{1}\bigl((\ln t)^{\nu -1}B^{d}( \ln t)\bigr) \biggr]. \end{aligned}$$
(54)

Case III. If we put \(g(t,\tau, \gamma )=\frac{t^{\gamma}-\tau ^{\gamma}}{\gamma}\) in Corollaries 3.1, 3.2, we will obtain the integral inequalities due to Nizar et al. [22].

Case IV. If \(g(t,\tau, \gamma )=\frac{t^{\gamma}-\tau ^{\gamma}}{\gamma}\) and \(\gamma =1\), then we obtain all the fractional inequalities introduced by Dahmani [4].

Case V. If we put \(g(t,\tau, \gamma )=\frac{t^{\gamma}-\tau ^{\gamma}}{\gamma}\) and \(\gamma =\lambda =1\), then all the outcomes will reduced to the traditional inequalities introduced in [3].

Conclusions

In the context of the generalized fractional theta-obedient integral, a variety of research directions related to integral inequalities can be examined in equation (12). More research on the Hermite–Hadamard inequality with differentiable h-convex functions [31], Hermite–Hadamard inequality for s-convex functions [29], the binary Brunn–Minkowski inequality [17], and other topics are predicted under this operator.

Availability of data and materials

The data that support the findings of this study are available from the authors upon request.

References

  1. Abdeljawad, T., Mohammed, P.O., Kashuri, A.: New modified conformable fractional integral inequalities of Hermite–Hadamard type with applications. J. Funct. Spaces 2020, 4352357 (2020)

    MathSciNet  MATH  Google Scholar 

  2. Alqudah, M.A., Kashuri, A., Mohammed, P.O., Abdeljawad, T., Raees, M., Anwar, M., Hamed, Y.S.: Hermite–Hadamard integral inequalities on coordinated convex functions in quantum calculus. Adv. Differ. Equ. 2021, 264 (2021)

    MathSciNet  Article  Google Scholar 

  3. Bougoffa, L.: On Minkowski and Hardy integral inequality. JIPAM. J. Inequal. Pure Appl. Math. 7, 60 (2006)

    MATH  Google Scholar 

  4. Dahmani, Z.: On Minkowski and Hermite–Hadamard integral inequalities via fractional integral. Ann. Funct. Anal. 1, 51–58 (2010)

    MathSciNet  Article  Google Scholar 

  5. Fernandez, A., Mohammed, P.: Hermite–Hadamard inequalities in fractional calculus defined using Mittag-Leffler kernels. Math. Methods Appl. Sci. 44, 8414–8431 (2021)

    MathSciNet  Article  Google Scholar 

  6. Guessab, A., Schmeisser, G.: Sharp integral inequalities of the Hermite–Hadamard type. J. Approx. Theory 115, 260–288 (2002)

    MathSciNet  Article  Google Scholar 

  7. Habib, S., Mubeen, S., Naeem, M.N.: Chebyshev type integral inequalities for generalized k-fractional conformable integrals. J. Inequal. Spec. Funct. 9, 53–65 (2018)

    MathSciNet  Google Scholar 

  8. Hadamard, J.: Étude sur les propriétés des fonctions entiéres en particulier d’une fonction considérée par Riemann. J. Math. Pures Appl. 58, 171–215 (1893)

    MATH  Google Scholar 

  9. Huang, C.J., Rahman, G., Nisar, K.S., Ghaffar, A., Qi, F.: Some inequalities of the Hermite–Hadamard type for k-fractional conformable integrals. Aust. J. Math. Anal. Appl. 16, 7 (2019)

    MathSciNet  MATH  Google Scholar 

  10. Hyder, A., Barakat, M.A.: Novel improved fractional operators and their scientific applications. Adv. Differ. Equ. 2021, 389 (2021)

    MathSciNet  Article  Google Scholar 

  11. Hyder, A.-A., Soliman, A.H.: A new generalized Θ-conformable calculus and its applications in mathematical physics. Phys. Scr. 96, 015208 (2020)

    Article  Google Scholar 

  12. Hyder, A.-A., Barakat, M.A., Fathallah, A., Cesarano, C.: Further Integral Inequalities through Some Generalized Fractional Integral Operators. Fractal Fract. 5, 282 (2021)

    Article  Google Scholar 

  13. Jarad, F., Uğurlu, E., Abdeljawad, T., Baleanu, D.: On a new class of fractional operators. Adv. Differ. Equ. 2017(1), 247 (2017)

    MathSciNet  Article  Google Scholar 

  14. Khan, M.B., Noor, M.A., Mohammed, P.O., et al.: Some integral inequalities for generalized convex fuzzy-interval-valued functions via fuzzy Riemann integrals. Int. J. Comput. Intell. Syst. 14, 158 (2021)

    Article  Google Scholar 

  15. Khan, M.B., Srivastava, H.M., Mohammed, P.O., Guirao, J.L.G.: Fuzzy mixed variational-like and integral inequalities for strongly preinvex fuzzy mappings. Symmetry 13, Article ID 1816 (2021)

    Article  Google Scholar 

  16. Khan, M.B., Srivastava, H.M., Mohammed, P.O., Macías-Díaz, J.E., Hamed, Y.S.: Some new versions of integral inequalities for log-preinvex fuzzy-interval-valued functions through fuzzy order relation. Alex. Eng. J. 61, 7089–7101 (2022)

    Article  Google Scholar 

  17. Lai, D., Jin, J.: The dual Brunn–Minkowski inequality for log-volume of star bodies. J. Inequal. Appl. 2021, 112 (2021)

    MathSciNet  Article  Google Scholar 

  18. Migórski, S., Khan, A.A., Zeng, S.: Inverse problems for nonlinear quasi-hemivariational inequalities with application to mixed boundary value problems. Inverse Probl. 36, 024006 (2020)

    MathSciNet  Article  Google Scholar 

  19. Mohammed, P.O., Abdeljawad, T.: Modification of certain fractional integral inequalities for convex functions. Adv. Differ. Equ. 2020, 69 (2020)

    MathSciNet  Article  Google Scholar 

  20. Mohammed, P.O., Sarikaya, M.Z.: On generalized fractional integral inequalities for twice differentiable convex functions. J. Comput. Appl. Math. 372, 112740 (2020)

    MathSciNet  Article  Google Scholar 

  21. Mubeen, S., Habib, S., Naeem, M.N.: The Minkowski inequality involving generalized k-fractional conformable integral. J. Inequal. Appl. 2019, 81 (2019)

    MathSciNet  Article  Google Scholar 

  22. Nisar, K.S., Tassaddiq, A., Rahman, G., Khan, A.: Some inequalities via fractional conformable integral operators. J. Inequal. Appl. 2019, 217 (2019)

    MathSciNet  Article  Google Scholar 

  23. Özdemir, M.E., Yıldız, C., Akdemir, A.O., Set, E.: On some inequalities for s-convex functions and applications. J. Inequal. Appl. 2013, 333 (2013)

    MathSciNet  Article  Google Scholar 

  24. Rahman, G., Nisar, K.S., Ghanbari, B., Abdeljawad, T.: On generalized fractional integral inequalities for the monotone weighted Chebyshev functionals. Adv. Differ. Equ. 2020, 368 (2020)

    MathSciNet  Article  Google Scholar 

  25. Rahman, G., Nisar, K.S., Qi, F.: Some new inequalities of the Grüss type for conformable fractional integrals. AIMS Math., 3(4), 575–583 (2018) https://doi.org/10.3934/Math.2018.4.575

    Article  MATH  Google Scholar 

  26. Rahman, G., Ullah, Z., Khan, A., Set, E., Nisar, K.S.: Certain Chebyshev-type inequalities involving fractional integral operators. Mathematics 7(4), 364 (2019). https://doi.org/10.3390/math7040364

    Article  Google Scholar 

  27. Samko, S.G., Kilbas, A.A., Marichev, O.I.: Fractional Integrals and Derivatives: Theory and Applications. Gordon & Breach, Reading (1993)

    MATH  Google Scholar 

  28. Set, E., Özdemir, M.E., Sarıkaya, M.Z.: Inequalities of Hermite–Hadamard’s type for functions whose derivatives absolute values are m-convex. AIP Conf. Proc. 1309, 861–873 (2010)

    Article  Google Scholar 

  29. Sezer, S.: The Hermite–Hadamard inequality for s-convex functions in the third sense. AIMS Math. 6, 7719–7732 (2021)

    MathSciNet  Article  Google Scholar 

  30. Srivastava, H.M., Sahoo, S.K., Mohammed, P.O., Baleanu, D., Kodamasingh, B.: Hermite–Hadamard type inequalities for interval-valued preinvex functions via fractional integral operators. Int. J. Comput. Intell. Syst. 15, 8 (2022)

    Article  Google Scholar 

  31. Yang, Y., Saleem, M.S., Ghafoor, M., Qureshi, M.I.: Fractional integral inequalities of Hermite–Hadamard type for differentiable generalized h-convex functions. J. Math. 2020, 2301606 (2020)

    MathSciNet  MATH  Google Scholar 

  32. Zeng, S., Gasiński, L., Winkert, P., Bai, Y.: Existence of solutions for double phase obstacle problems with multivalued convection term. J. Math. Anal. Appl. 501, 123997 (2021)

    MathSciNet  Article  Google Scholar 

Download references

Acknowledgements

The authors extend their appreciation to the Deanship of Scientific Research at King Khalid University for funding this work through Research Groups Program under grant RGP.2/15/43.

Funding

This research was funded by King Khalid University, grant RGP.2/15/43.

Author information

Authors and Affiliations

Authors

Contributions

The manuscript was written by AH, MAB, and AF. AH was also responsible of acquiring finance. AH and MAB worked together to accomplish the formal analysis, writing the review, and editing. All authors read and approved the final manuscript.

Corresponding author

Correspondence to M. A. Barakat.

Ethics declarations

Ethics approval and consent to participate

Not applicable.

Consent for publication

Not applicable.

Competing interests

The authors declare that they have no competing interests.

Rights and permissions

Open Access This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/.

Reprints and Permissions

About this article

Verify currency and authenticity via CrossMark

Cite this article

Hyder, AA., Barakat, M.A. & Fathallah, A. Enlarged integral inequalities through recent fractional generalized operators. J Inequal Appl 2022, 95 (2022). https://doi.org/10.1186/s13660-022-02831-y

Download citation

  • Received:

  • Accepted:

  • Published:

  • DOI: https://doi.org/10.1186/s13660-022-02831-y

Keywords

  • Generalized fractional operators
  • Integral inequalities
  • Hermite–Hadamard inequalities
  • Minkowski inequalities